A new genus with three new species of free-living marine nematodes of the subfamily Desmodorinae (Nematoda: Desmodoridae), from the continental shelf off northeastern Brazil - Larrazábal-Filho, Alexandre L.; Neres, Patrícia F.; Da Silva, Maria Cristina; Esteves, André M. (Zootaxa, 2019)
Three new species representing a new genus of marine nematodes were collected on the continental shelf of the Potiguar Basin, northeastern Brazil. Spinonema gen. n. has a coarsely annulated cuticle with the inner layer ornamented with vacuoles, and lateral alae. The lateral alae are formed by raised and bent lateral sections of annules, resembling the letter C. C-shaped refers to each individual segment of ala. Some species have a dorsal spine, arched spicules and a well-developed head capsule, with a thick cuticle without annulations. Spinonema gen. n. has some features in common with certain genera of the family Desmodoridae but can be distinguished by the coarse body annuli, cuticular ornamentation (lateral alae, and in some species a dorsal spine) and the absence of subcephalic setae. The type species of the new genus, Spinonema cuticulatum gen. et sp. n., is characterized by the presence of a spiral fovea amphidialis, hook-shaped spicules in the capitulum, a velum and three ejaculatory glands. Spinonema spirale gen. et sp. n. has body annuli with the inner cuticle ornamented with vacuoles along the entire body, a multispiral fovea amphidialis with 3.15 turns and a gubernaculum intricate, with lateral crurae. Dorsal apophysis of gubernaculum wing-shaped. Spinonema absente gen. et sp. n. has a cryptospiral fovea amphidialis, short spicules, a simple gubernaculum and three precloacal setae.